(untitled) (Altre Modernità, 2022)
Since the beginning of the Covid-19 lockdown in March 2020, Italian universities have been faced with a completely new situation, generally marked by a certain backwardness as regards distance language teaching. This paper describes the impact that distance learning has had on language teaching, particularly on the teaching of lexis in the first year of a three-year degree course in Arabic at Roma Tre University, Italy. Learning vocabulary is a vital part of mastering a language, and experience has shown that students often do not work methodically on this aspect, which leads to problems with listening, speaking, reading, and writing skills. Online teaching has only aggravated this situation and, consequently, new approaches and methodologies are required. This case study presents solutions that have been found in adopting MOODLE, the open-source platform that provides students with a dynamic instrument aimed at facilitating learning. In particular, it describes and evaluates the use of the glossary in MOODLE to help first-year students learn Arabic vocabulary. The students had to add 20 vocabulary items to the glossary each week, and contributions had to follow a certain format that required morphological awareness of the main Arabic lexical structures. The monitoring system whereby the teacher could view student activities further bolstered the learner-centered methodology upon which the whole system is based. Results showed that all students contributed to creating an instrument that promoted independent learning. Overall, the MOODLE glossary was a useful tool for vocabulary learning and recommendations for its successful implementation are reported. This case study will be of interest to language teachers, as well as to learners and instructors dealing with specialized terminology.